Design of a Circularly Polarized -Slot Antenna with Isotropic Pattern for the UHF RFID Reader of WSN - Jongan Park; Jonghun Chun; Gwangwon Kang; Sungkwan Kang; Youngeun An (International Journal of Distributed Sensor Networks)
In an antenna for a UHF RFID reader of wireless sensor networks (WSN), receiver sensitivity in sensing multitags from remote distances is an important performance index. This study designed a dual structured Z -slot antenna with optimized receiver sensitivity to enhance the sensitivity to a circularly polarized antenna with an isotropic pattern for a UHF RFID. Through analysis of performance in the designed antenna, the following was verified: return loss ( S 11 ) was about −62.21 dB at 925.25 MHz, antenna gain was 7.36 dBi, and Δ P r , isotropic gain deviation, was 1.3 dB. Impedance matching was about 50.069 Ω at 925.25 MHz and VSWR was from 1.001 to 1.028. Through this research it was discovered that this can be applied to the design of all RFID readers of WSN. Based on the above results, it is suggested that a circularly polarized Z -slot antenna which can enhance receiver sensitivity over a wide range can be widely applied to UHF RFID readers of WSN.